(untitled) (Journal of the College of Basic Education, 2024)
The study aimed to evaluate the efficiency of vacuum treatment with carbon dioxide gas in controlling the different stages of the fig moth, Cadra cautella (Pyralidae: Lepidoptera) that infect dates in storage. The results showed an evaluation of the efficiency of vacuum treatment with 50% and 100% second gas concentration Carbon oxide, individually, in controlling the of different stage( adults, pupae, larvae and eggs) that infect dates in the storage. The percentage of mortality increases with increasing concentration of carbon dioxide gas, as the percentage of mortality for adults, pupae, and larvae reached 100%, 70.00%, and 100%, respectively, at a concentration of 100% carbon dioxide gas at an exposure period of 240 minutes and after one day of exposure. The study also showed that exposing eggs to vacuum treatment with 100% carbon dioxide gas for a period of 240 minutes led to an inhibition of the egg hatching percentage reached 62.95%, while the lowest rate of inhibition of the egg hatching percentage was at a 30-minute exposure period, which reached 16.66%.